2011
DOI: 10.1177/1948550611398416
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Rules to Rise to Power

Abstract: Powerful people often act at will, even if the resulting behavior is inappropriate-hence the famous proverb ''power corrupts.'' Here, we introduce the reverse phenomenon-violating norms signals power. Violating a norm implies that one has the power to act according to one's own volition in spite of situational constraints, which fuels perceptions of power. Four studies support this hypothesis. Individuals who took coffee from another person's can (Study 1), violated rules of bookkeeping (Study 2), dropped ciga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 39 publications
4
69
3
Order By: Relevance
“…Previous research provides some suggestive evidence that power shapes individuals' anger expression, but the results are inconclusive. On the one hand, studies on emotional stereotypes associated with power and status revealed that people expect individuals with high power or status to respond with anger when negative outcomes occur, whereas they expect individuals with low power or status to respond with sadness and guilt (Tiedens, Ellsworth, & Mesquita, 2000;Van Kleef, Homan, Finkenauer, G€ undemir, & Stamkou, 2011). On the other hand, research involving actual anger experience and expression of high-and low-power individuals revealed that, during a controversial group discussion, powerless participants experienced and expressed more anger than did powerful ones (Berdahl & Martorana, 2006).…”
Section: Data Archiving and Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research provides some suggestive evidence that power shapes individuals' anger expression, but the results are inconclusive. On the one hand, studies on emotional stereotypes associated with power and status revealed that people expect individuals with high power or status to respond with anger when negative outcomes occur, whereas they expect individuals with low power or status to respond with sadness and guilt (Tiedens, Ellsworth, & Mesquita, 2000;Van Kleef, Homan, Finkenauer, G€ undemir, & Stamkou, 2011). On the other hand, research involving actual anger experience and expression of high-and low-power individuals revealed that, during a controversial group discussion, powerless participants experienced and expressed more anger than did powerful ones (Berdahl & Martorana, 2006).…”
Section: Data Archiving and Sharingmentioning
confidence: 99%
“…On the one hand, studies on emotional stereotypes associated with power and status revealed that people expect individuals with high power or status to respond with anger when negative outcomes occur, whereas they expect individuals with low power or status to respond with sadness and guilt (Tiedens, Ellsworth, & Mesquita, 2000;Van Kleef, Homan, Finkenauer, G€ undemir, & Stamkou, 2011). On the one hand, studies on emotional stereotypes associated with power and status revealed that people expect individuals with high power or status to respond with anger when negative outcomes occur, whereas they expect individuals with low power or status to respond with sadness and guilt (Tiedens, Ellsworth, & Mesquita, 2000;Van Kleef, Homan, Finkenauer, G€ undemir, & Stamkou, 2011).…”
mentioning
confidence: 99%
“…People may see criminal offenders' status, or hierarchical position, as having implications for their hierarchy preferences. Because offenders gain power and status by degrading victims (Bilz, 2016;Van Kleef et al, 2011), low-status offenders may seem to threaten or attenuate hierarchies by redistributing power to lower ranks, and high-status offenders may seem to enhance hierarchies by distributing or maintaining power at higher ranks. If so, then retribution should be differentially supported depending on whether offenders threaten the perceiver's preferred societal structure: People who prefer relatively egalitarian societies may support greater retribution against high-status offenders, and people who prefer relatively hierarchical societies may support greater retribution against low-status offenders.…”
Section: Offender Statusmentioning
confidence: 99%
“…One set of studies showed that individuals who violated prevailing norms were perceived as more powerful than individuals who behaved according to the norms (van Kleef, Homan, Finkenauer, Gündemir, & Stamkou, 2011). Another series of studies showed that individuals who entered a boutique wearing gym clothes rather than appropriate attire or who attended a black tie event wearing a red rather than a black tie were ascribed higher status (Bellezza, Gino, & Keinan, 2014).…”
Section: Social Norms and Reactions To Norm Violationsmentioning
confidence: 99%